A new approach in cancer treatment: poly (ADP-ribose) polymerase-1 inhibitors - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (AVES PRESS LTD, 2015)
Internal and external factors can damage DNA, the genetic material. Numerous repair mechanisms, which can repair those damages, exist in the normal cell. One of those is called PARP-1 enzyme. PARP-1 transfers ADP-ribose subunits from nicotinamide adenine nucleotide to protein acceptor. Thus, single strand DNA breaks can be repaired. If PARP-1 inhibition occurs, single strand DNA breaks cannot be repaired and double strand DNA breaks can be formed. Eventually, cells undergo necrosis or apoptosis. The aim of cancer treatment is to inhibit the PARP-1 enzyme. For this purpose, many studies have been published over the last decade and currently PARP-1 enzyme inhibitors which are in the phase studies and which are waiting to be marketed are available. In this review, information are given for the mechanisms by which DNA damage is repaired, the protection mechanism of the genomic integrity of PARP enzyme family and chemical structure of PARP-1 inhibitors which are improved to use in cancer treatment.
Keywords: Poly(ADP-ribose) polymerase; molecular modelling; PARP-1 inhibitors; cancer treatment